2021
DOI: 10.1089/pop.2019.0205
|View full text |Cite
|
Sign up to set email alerts
|

Initiating and Implementing Social Determinants of Health Data Collection in Community Health Centers

Abstract: Successfully incorporating social determinants of health (SDH) screening into clinic workflows can help care teams provide targeted care, appropriate referrals, and other interventions to address patients' social risk factors. However, integrating SDH screening into clinical routines is known to be challenging. To achieve widespread adoption of SDH screening, we need to better understand the factors that can facilitate or hinder implementation of effective, sustainable SDH processes. The authors interviewed 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…Participants noted the importance of having leadership support for this work, which has previously been identified as a facilitator of successful SDOH screening in community health centers. 26 Additionally, resource staff described how a trusting relationship with patients facilitated their ability to address social needs. A qualitative study of patients receiving assistance for SDOH from volunteers reported that the connection with the staff helped them to feel heard and supported.…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted the importance of having leadership support for this work, which has previously been identified as a facilitator of successful SDOH screening in community health centers. 26 Additionally, resource staff described how a trusting relationship with patients facilitated their ability to address social needs. A qualitative study of patients receiving assistance for SDOH from volunteers reported that the connection with the staff helped them to feel heard and supported.…”
Section: Discussionmentioning
confidence: 99%
“…25 CHC patients in particular face many adverse social determinants that impede their ability to seek needed preventive care, thus impacting clinical performance. Although CHCs screen for social needs more than non-CHC practices, 26 many barriers (e.g., inadequate reimbursement, resources) 27,28 to successful implementation and sustainability of social needs screening/referral exist. Health policies focusing on adequate reimbursement for screening and referral and financial assistance for staff training and resources are critical for sustaining this service.…”
Section: Article In Pressmentioning
confidence: 99%
“…Organizational readiness for social needs screening, including wide‐scale training of interprofessional teams, utilization of training modules, and strategic workflow design have been advocated as a more durable, pragmatic, and ethically sound approach to ED‐based social care 33‐35 . However, even a “perfect” social care system in the ED may fail at times, and most pediatric EDs remain without an integrated social care system as evidenced by our study.…”
Section: Discussionmentioning
confidence: 75%
“…[30][31][32][33] A crucial step in that evolution is as a more durable, pragmatic, and ethically sound approach to EDbased social care. [33][34][35] However, even a "perfect" social care system in the ED may fail at times, and most pediatric EDs remain without an integrated social care system as evidenced by our study. Although fellows were more likely to have received formal training in SDH or social needs screening and referral compared to PDs, both groups expressed very similar rates of low comfort with and high value of social care practice.…”
Section: Discussionmentioning
confidence: 98%